Performance evaluation and thermal analysis of pottery furnace in Thimi, Bhaktapur - Adhikari, Ushan; Prajapati, Bijendra; Bhandari, Anil Mani (Journal of Innovations in Engineering Education, 2021)
Pottery is a unique art that involves creating items out of clay. It creates a variety of clay and ceramic products, including as flowerpots, water and grain storage jars, by distilling rice spirits. Almost all pottery manufacture is done in the conventional manner, which uses more energy and emits hazardous emissions. This project primarily focuses on experimental performance analysis, calculating temperature distribution, fuel required per batch, pottery production per batch, maximum temperature reading, flame temperature, and energy audit for an existing furnace and thermal analysis of pottery furnace giving optimum design for future construction and modification of existing furnace. Energy calculation shows that specific fuel consumption of different furnaces in Thimi varies from 0.98MJ/kg to 2.4MJ/kg. Experimental data are collected and validated by transient thermal analysis using ANSYS.